THE IMPACT OF SOCIAL FACTORS AND CURRICULUM ON THE ENTREPRENEURIAL INTENTIONS OF MUSLIM STUDENTS - Hendra Cipta; Hatamar Hatamar (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
This study looks into how social factors like social interaction, family support, and career orientation, along with curriculum elements, especially the implementation of the Merdeka Belajar-Kampus Merdeka Curriculum (MBKM), influence the entrepreneurial intentions of students at Islamic religious universities in Indonesia. The research uses a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. A total of 392 students from ten Islamic religious universities across Indonesia took part in the study. The findings revealed that social interaction and family support had a significant impact on students' entrepreneurial intentions, whereas career orientation did not have a notable effect. The introduction of the MBKM curriculum greatly boosts students' entrepreneurial intentions. These results provide both theoretical insights and practical guidance for promoting entrepreneurship in Islamic religious universities. They highlight the importance of MBKM policies, reinforced by social factors such as social interaction and family support, in nurturing students' entrepreneurial spirit. Therefore, combining the MBKM curriculum with a supportive social environment could be an effective strategy to build an entrepreneurial ecosystem within Islamic religious universities in Indonesia.